2020
DOI: 10.14214/sf.10196
|View full text |Cite
|
Sign up to set email alerts
|

Low cost prediction of time consumption for pre-commercial thinning in Finland

Abstract: The time consumption (TC) of pre-commercial thinning (PCT) varies greatly among sites, stands and forest workers. The TC in PCT is usually estimated by field-assessed work difficulty factors. In this study, a linear mixed model for the TC in PCT was prepared by utilizing forest resources data (FRD). The modelling data included 11 848 and validation data included 3035 worksites with TC information recorded by forest workers within the period of 2008–2018. The worksites represented a range of site and stand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
(27 reference statements)
2
8
0
Order By: Relevance
“…We also found that the time consumption of EC depended on the elevation changes (H3b) and wetness of a site (H3c). Similar findings have previously been observed with elevation changes in Hämäläinen and Kaila (1983), and with wetness in Uotila et al (2020).…”
Section: Time Consumption and Costs In A Juvenile Stand Management Programsupporting
confidence: 90%
See 4 more Smart Citations
“…We also found that the time consumption of EC depended on the elevation changes (H3b) and wetness of a site (H3c). Similar findings have previously been observed with elevation changes in Hämäläinen and Kaila (1983), and with wetness in Uotila et al (2020).…”
Section: Time Consumption and Costs In A Juvenile Stand Management Programsupporting
confidence: 90%
“…Depending on the cleaning method, the seasonal timing of EC could contribute to worktime consumption fluctuations of between 27 and 30%. Uotila et al (2020) found a similar difference in worktime fluctuations between seasons in cross-sectional data. In small cross-sectional data, Hämäläinen and Kaila (1983) also found that PCT in the spring was more productive than in the summer.…”
Section: Time Consumption and Costs In A Juvenile Stand Management Programsupporting
confidence: 59%
See 3 more Smart Citations